Encouraging Employee Performance with Occupational Safety and Occupational Health - Saleh Tutupoho; Wylda Olivia Kowey (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research was conducted based on the phenomenon of Health Workers at the Ambon City Health Office with suggestions regarding the problems faced by Ambon City Health Workers during the Covid-19 Pandemic by knowing the Effect of Occupational Health and Occupational Safety on the Performance of Ambon City Health Workers. The type of research used is quantitative research using primary data with interviews and questionnaires. Systematically based on the research objectives of the Ambon City Health Office Health Workers. The sample collection technique in this study uses the saturated sampling method, where all members of the population are sampled. The results showed that the occupational health variable had a positive and significant effect on the performance of the Ambon City Health Office.